(untitled) (Eurasian Research Bulletin, 2023)
The work is based on the analysis of studies conducted in 60 patients who underwent inpatient treatment in the general resuscitation department of the Republican Scientific Center for Emergency Medical Care and in the hepatology department of the regional infectious diseases hospital of Bukhara region for the period from 2021 to 2023.